SEROLOGICAL STUDY ON THE PREVALENCE OF MYCOMPLASMA GALLISEPTICUM IN BROILER - A. H Shalash, A.; A. H. Zahid. , A. (The Iraqi Journal of Veterinary Medicine, 1989)
Both rapid serum plate agglutination test (RSPT) and Haemagglutination Inhibition test (HIT) were utilized in this study. Serological data are presented for 244 blood that were collected and examined for the detection of Mycomplasma gallisepticum antibodies from 25 to 39 days old broiler chicks. 55.6% of the samples reacted positively by using RSPT while 36.9% of the samples reacted positively by using HIT. From results obtained in this study it would appear that the sensitivity of RSPT and HIT is unequal.